Monocyte subsets predict mortality after cardiac arrest. (25th November 2020) - Krychtiuk, K.A; Lenz, M; Richter, B; Huber, K; Wojta, J; Hengstenberg, C; Heinz, G; Speidl, W.S
Abstract: Background: After successful cardiopulmonary resuscitation with return of spontaneous circulation (ROSC), many patients show signs of an overactive immune activation. Monocytes are a heterogenous cell population that can be distinguished into three subsets. Purpose: The aim of this prospective, observational study was to analyze whether monocyte subset distribution is associated with mortality at 6 months in patients after cardiac arrest. Methods: We included 53 patients admitted to our medical ICU after cardiac arrest. Blood was taken on admission and monocyte subset distribution was analyzed by flow cytometry and distinguished into classical monocytes (CM; CD14++CD16-), intermediate monocytes (IM; CD14++CD16+CCR2+) and non-classical monocytes (NCM; CD14+CD16++CCR2-). Results: Median age was 64.5 (IQR 49.8–74.3) years and 75.5% of patients were male. Mortality at 6 months was 50.9% and survival with good neurological outcome was 37.7%. Of interest, monocyte subset distribution upon admission to the ICU did not differ according to survival. However, patients that died within 6 months showed a strong increase in the pro-inflammatory subset of intermediate monocytes (8.3% (3.8–14.6)% vs. 4.1% (1.5–8.2)%; p=0.025), and a decrease of classical monocytes (87.5% (79.9–89.0)% vs. 90.8% (85.9–92.7)%; p=0.036) 72 hours after admission. In addition, intermediate monocytes were predictive of outcome independent of initial rhythm and time to ROSC and correlated with the CPC-score at 6 months (R=0.32; p=0.043). Discussion: Monocyte subset distribution is associated with outcome in patients surviving a cardiac arrest. This suggests that activation of the innate immune system may play a significant role in patient outcome after cardiac arrest. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): FWF - Fonds zur Förderung der wissenschaftlichen Forschung